Student Pharmacists' Perceptions of Amazon Pharmacy - Alexandra Stich; Christian Cava; Dominic Cava; David R. Axon (MDPI AG, 2021)
Amazon recently launched their online pharmacy in the United States (US). However, no studies have explored student pharmacists' perceptions of the potential impact of Amazon Pharmacy. This qualitative study used individual semi-structured interviews to examine third- and fourth-year student pharmacists' perceptions of how Amazon Pharmacy will affect economic, clinical, and humanistic outcomes; the pharmacy experience; and the job market. Interviews were audio-recorded, transcribed verbatim, and thematically analyzed by two independent reviewers until saturation was reached, with differences resolved through discussion with a third researcher. Seventeen students participated in the study. Five themes were identified: perceived economic outcomes for patients, perceived clinical outcomes for patients, perceived humanistic outcomes for patients, perceived impact of the pharmacy experience for patients, and perceived influence of Amazon Pharmacy on the pharmacy market. The majority suggested Amazon Pharmacy would offer lower costs for patients (71%), improved medication adherence (76%), and improved quality of life (65%). There was a consensus that the Amazon Pharmacy experience would be different, with various opinions highlighting potential positive or negative aspects of the service. There were mixed opinions about job opportunities and impact on existing pharmacies. Future studies should evaluate economic, clinical, and humanistic outcomes for patients utilizing Amazon Pharmacy.